Oxidizing Effect of the Cu(ClO4)2 on Chemical Polymerization of Aniline in Anhydrous Media - CAN, MUZAFFER; UZUN, SULTAN (Asian Journal of Chemistry, 2010)
The oxidative effect of copper(II) perchlorate [Cu(ClO4)2] on chemical polymerization of aniline was elucidated by using experimental methods such as conductivity measurements, thermogravimetric analysis, UVvisible and FTIR spectroscopy. Experimental studies indicate that copper(II) perchlorate can be used as oxidant in the chemical polymerization of aniline at the ratio of aniline-Cu(ClO4)2 is 1:1.